Zorotypus in Peninsular Malaysia (Zoraptera: Zorotypidae), with the description of three new species - Mashimo, Yuta; Yoshizawa, Kazunori; Engel, Michael S.; Ghani, Idris Abd.; Dallai, Romano; Beutel, Rolf G.; Machida, Ryuichiro (Zootaxa, 2013)
Three new species of the uncommonly encountered insect order Zoraptera are described and figured from Peninsular Malaysia—Zorotypus magnicaudelli sp. n., Zorotypus cervicornis sp. n., and Zorotypus impolitus sp. n. Another species from the region, identified as Zorotypus caudelli Karny, 1927, was also collected and is reevaluated herein based on new material. A brief discussion of characters used in zorapteran systematics is provided, and a key to the species of Peninsular Malaysia provided. This is the first report for the order Zoraptera from Peninsular Malaysia.